A novel photoelectrooptical effect based on Freedericksz-type transition in nematic mixtures of azoxy compounds and cyanobiphenyls - Lisetski, L.N.; Samoilov, A.N.; Minenko, S.S.; Fedoryako, A.P.; Bidna, T.V. (Functional Materials, 2018)
In mixtures of nematic liquid crystals with opposite signs of dielectric anisotropy (alkylcyanobiphenyls and azoxybenzenes), a possibility of photoinduced Freedericks-type transition was realized, which could be observed both by optical transmission in a standard geometry and by changes in electric conductivity. UV irradiation leads to lowering of the planar-to-homeotropic transition threshold, and at a certain bias voltage a photoinduced transition could be realized. Trans-cis isomerization of azoxy component decreases the anisometry of its molecules, resulting in higher positive dielectric anisotropy of the material. Prospects of application of the reported effect in optoelectronic devices are discussed.